The Influence of Social Media in Era 4.0 in Criminal Law Study and Implementation of Criminal Sanctions - Aryo Fadlian (IJCLS (Indonesian Journal of Criminal Law Studies), 2022)
The purpose of the author is to provide an understanding and prevention of the dangers of social media. The times have pushed all fields in a country, one of which is the development of digital technology. Digital technology, which we know, is one form of civilization that is very looming in the community, to facilitate all one's activities. The use of social media that spreads and frees its users to carry out activities on social media, then there are no boundaries in social media except self-control. Seeing these gaps from a social media can be a place where criminal acts can occur and do not know the class of people who use social media. Social media is a form of information technology as regulated in Law Number 11 of 2008 concerning Information and Electronic Transactions in article 1 number 3 which reads: "a technique for collecting, preparing, storing, processing, announcing, analyzing, and/or or disseminate information.”. because of what has been explained in the ITE law.